GENETIC DIVERSITY OF IRAQI LOCAL GOAT BREEDS BY RAPD DNA MARKERS - Awat Nooradin Yousif; Mohammed Abdalla (Universitas Syiah Kuala, 2022)
Genetic diversity of three Iraqi local goat breeds (Black, Hybrid, and Meriz) was studied by using random amplified polymorphic DNA (RAPD) markers. Fifteen primers were used, they generated a total of 259 amplification products, from which 142 bands were polymorphic, revealing 55.29% polymorphism. It was found that the mean value of Nei’s gene diversity (h) and Shannon's ınformation index (I) were 0.1778 and 0.2546, respectively. According to the analysis of genetic distances among breeds, the highest genetic distance recorded between Black and Hybrid 0.5108, while the lowest genetic distance recorded between Hybrid and Meriz 0.1431. The phylogenetic dendrogram based on Nei’s genetic distance analysis was in agreement with their phenotypic similarities in which the tree separated the surveyed breeds into two clusters, the first one including Black goat breed, and the second cluster includes Hybrid and Meriz breeds. These results indicated that Black goat breed is most genetically distant from both Hybrid and Meriz breeds. Finally, the moderate value for both of polymorphism and genetic diversity which obtained from the present study indicate that these breeds are genetically different, which provide a good background about these breeds for genetic improvement and conservation of our local goat breeds in the future.